2019
DOI: 10.1007/s00429-019-01985-8
|View full text |Cite
|
Sign up to set email alerts
|

Fiber dissection and 3-tesla diffusion tensor tractography of the superior cerebellar peduncle in the human brain: emphasize on the cerebello-hypthalamic fibers

Abstract: Experimental studies in various species using tract-tracing techniques showed clear evidence of the presence of cerebellohypothalamic projections. However, these connections were not clearly described in humans. In the present study we aimed to describe the direct cerebello-hypothalamic connections within the superior cerebellar peduncle (SCP) using fiber dissection techniques on cadaveric brains and diffusion tensor tractography (DTI) in healthy adults. Fiber dissection was performed in a stepwise manner from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“… 61 The SCP is the main WM tract by which information from the cerebellum transmits to the rest of the brain, connecting the cerebellum to the midbrain, basal ganglia 64 , 65 and hypothalamus. 66 WM microstructure of the SCP has been shown to be associated with proprioception in non-autistic adults, 67 motor skills in autistic children, 68 and motor skills, expressive language, and IQ in preterm-born children (some of whom were autistic). 69 In the present study, we found corroborating evidence for the role of the SCP in motor and communication skills in that there were overlapping ODI and ICVF clusters in the right SCP associated with motor ability as well as a cluster in the superior portion of the SCP associated with autism symptom severity change.…”
Section: Discussionmentioning
confidence: 99%
“… 61 The SCP is the main WM tract by which information from the cerebellum transmits to the rest of the brain, connecting the cerebellum to the midbrain, basal ganglia 64 , 65 and hypothalamus. 66 WM microstructure of the SCP has been shown to be associated with proprioception in non-autistic adults, 67 motor skills in autistic children, 68 and motor skills, expressive language, and IQ in preterm-born children (some of whom were autistic). 69 In the present study, we found corroborating evidence for the role of the SCP in motor and communication skills in that there were overlapping ODI and ICVF clusters in the right SCP associated with motor ability as well as a cluster in the superior portion of the SCP associated with autism symptom severity change.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a direct cerebello-hypothalamic tract was described in Human. Indeed, DTI results reported fibers projecting from the cerebellar nuclei to the contralateral anterior HT and ipsilateral posterior HT ( 83 ). The cerebellar-hypothalamic connection seems to allow for the convergence of non-limbic information to the limbic system through the hypothalamic and septal nuclei.…”
Section: Structural Connectivity Of Hypothalamusmentioning
confidence: 99%
“…Even if less frequently reported in comparison with the supratentorial compartment, in-vivo and ex-vivo methods were also adopted for investigating cerebellar WM anatomy. The most recent available studies reported detailed exposition and threedimensional representation of different gray and WM structures, focusing on reciprocal relationships and practical surgical implications, mainly concerning the indications, advantages, limitations, and possible risks of specific approaches (32)(33)(34)(35)(36).…”
Section: The Cerebellar Connectome Historymentioning
confidence: 99%
“…For example, several Authors discussed about existence and functional role of reciprocal connections between the cerebellum and the hypothalamus. After previous evidence in animal models using track-tracing and electrophysiology methods, direct cerebello-hypothalamic connections passing through the SCP have been recently described also in the human brain using fiber dissection and DTI technique (2,32,75,76). Even if the functional orientation (afferent or efferent) of this pathway needs to be clarified, these results would confirm the effective participation of the cerebellum in typical hypothalamic processing, such as cardiovascular osmolarity regulation, feeding behavior, energy balance, and weight control (77,78).…”
Section: Cerebellum and Neurocognitive Development Functional Anatomy...mentioning
confidence: 99%